1911
DOI: 10.5962/bhl.title.20756
|View full text |Cite
|
Sign up to set email alerts
|

The maturation of the egg of the mouse, by J. A. Long and E. L. Mark.

Abstract: CARNEGIE INSTITUTION OF WASHINGTON, PUBLICATION No. 142 CONTRIBUTIONS FROM ZOOLOGICAL LABORATORY OF THE MUSEUM OF COMPARATIVE ZOOLOGY AT HARVARD COLLEGE. E. L. MARK, DIRECTOR. No. 216. Copies of this Book were first issued APR 3 191J PRESS OF J. B. LIPPINCOTT COMPANY PHILADELPHIA 41 First polar cell 41 Second polar cell 44 VIII. Criticisms and conclusions 45 A. Material 45 B. Methods 45 C. Time relations 46 D. Ovulation Chromatin Achromatin Centrosomes, circumpolar bodies, and clear region Position and orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

1931
1931
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
5
1
Order By: Relevance
“…A similar phenomenon was noted in the rat (Austin and Braden 1954b) and it was suggested that maturation of the egg membranes after ovulation was necessary before sperm penetration could occur. Long and Mark (1911) thought that the pronuclei were formed within a few minutes of sperm penetration in the mouse; however, the present observations show that this is not so. Sobotta (1895) concluded that the interval required was of the order of 1 hr, but even this estimate appears to be low.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A similar phenomenon was noted in the rat (Austin and Braden 1954b) and it was suggested that maturation of the egg membranes after ovulation was necessary before sperm penetration could occur. Long and Mark (1911) thought that the pronuclei were formed within a few minutes of sperm penetration in the mouse; however, the present observations show that this is not so. Sobotta (1895) concluded that the interval required was of the order of 1 hr, but even this estimate appears to be low.…”
Section: Discussioncontrasting
confidence: 56%
“…Comparison is difficult, however, because, in three instances, the first post-partum oestrus was used; the time relations of oestrus, ovulation, sperm transport, and the penetration of the eggs may well be different under such circumstances. The estimates given were 6-10 hr (Gerlach 1906), 4-7 hr (Long and Mark 1911), and 3-4 hr (Merton 1939). Mating at the second oestrus post-partum was employed by Sobotta (1895), whereas Lewis and Wright ( 1935) and the present authors used virgin females.…”
Section: Discussionmentioning
confidence: 99%
“…The homogeneous phase of tuberculosis, as disclosed by this study, seems to have been overlooked in most investigations of the immediate response to infection (9)(10)(11)(12). Possible reasons for this are: (1) methods used to induce infections may have implanted more than single organisms in the average focus, (2) the rate of tubercle development is not the same in all tissues, and (3) the rate of tubercle development may differ with the species.…”
Section: Discussionmentioning
confidence: 82%
“…The participation of polymorphonuclear leucocytes in the cellular response of experimental animals to the injection of tubercle bacilli was first convincingly demonstrated in the histological studies of Borrel (1) and has been investigated often during recent years. Thus it has been shown in guinea pigs and rabbits that the bacilli are phagocytized by polymorphonuclear leucocytes immediately upon coming into contact with these phagocytic cells and that the latter undergo a characteristic clumping, apparently as a result of engulfing the bacilli (2,3).…”
mentioning
confidence: 99%